TECHNOLOGY OF PARTNERSHIP: ITS ADVANTAGES AND CHALLENGES IN THE IMPLEMENTATION OF EDUCATIONAL PROGRAMS AT UNIVERSITY - K. L. Polupan (Высшее образование в России)
Nowadays the development of higher education is characterized by diversified research in the field of teaching technologies implementation. At the same time technologies of joint activities, and more specifically – achievement of a joint result is not under specific focus. In the article, based on the analysis of the distinctive features of partnership technology, the construct of the activity on the technology inoculation was drawn up and the structure of its effective implementation in the educational process was developed. To confirm the proposed approach methods of modeling, designing, direct and included surveillance, and diagnostics were implemented.